Residual behaviour of imidacloprid in the country bean growing soil - Rahman, H; Akter, T; Mishu, HK; Miah, RU; Alam, MS (Bangladesh Journal of Agricultural Research, 2019)
The assessment of residual behavior of imidacloprid (Admire 20SL) in the soil of country bean agroecosystem and its risk assessment for consumption was studied. QuEChERS method was used for the extraction and clean-up of samples and the residues of imidacloprid was estimated using Gas Chromatography. The dissipation studies in the soil system were carried out by application of imidacloprid at five different dosages i.e. 100, 200, 300, 400, and 500 g a.i. ha-1. Average initial deposits of imidacloprid were found to be 0.99, 1.33, 1.62, 1.83 and 2.20 mg.kg-1. The residues reached below determination limit (BDL) of 0.01 mg kg-1 in 9 days for recommended dose and 12 days for remaining higher dosages. Half-life (T1/2)) of imidacloprid in the soil was observed to be 1.88, 1.74, 1.73, 1.56 and 1.52 days for 100, 200, 300, 400, and 500 g a.i. ha-1, respectively. The chemodynamics study of imidacloprid spray indicated that only 27.20 -28.40% sprays were deposited to the target site (plant canopy) and 71.60-72.80% were lost to non-target site such as soil and air. The drift of imidacloprid to soil (39.47-40.20%) was higher than the air (32.13-32.60%). Based on degradation pattern and maximum, the recommended preharvest interval (PHI) might be eight 9 days and a waiting period of two days might be suggested for reapplication of the imidacloprid in country bean agroecosystem. Bangladesh J. Agril. Res. 44(1): 89-101, March 2019